2000
DOI: 10.1093/sleep/23.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Supine Cephalometric Study on Sleep-Related Changes in Upper-Airway Structures in Normal Subjects

Abstract: Abstract:The purpose of this study was to examine sleep-related changes in the upper airway and surrounding structures including the mandible, hyoid bone, and cervical vertebra in normal subjects using lateral cephalograms in the supine position. Eleven male and nine female healthy adults participated in this study. Supine cephalograms were taken at end-expiration during wakefulness and in stage 1-2 non-rapid-eye-movement (NREM) sleep judged from the electroencephalogram and respiratory monitoring. A paired t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…All of the cephalometric analyses were performed by the same orthodontist before the follow-up polysomnographic study. The value of method errors for the cephalometric analyses (range 0.25-0.63 mm) was consistent with those in previous studies [10,11].…”
Section: Supine Cephalometrysupporting
confidence: 90%
See 2 more Smart Citations
“…All of the cephalometric analyses were performed by the same orthodontist before the follow-up polysomnographic study. The value of method errors for the cephalometric analyses (range 0.25-0.63 mm) was consistent with those in previous studies [10,11].…”
Section: Supine Cephalometrysupporting
confidence: 90%
“…The authors accept that this study with twodimensional cephalometry has known limitations to measure the transverse dimension [25], cross-sectional shape [27] and volume [28] of the UA. However, as long as data are collected following a standardised method [5,10], the superimposition of cephalometric tracings appears to be useful enough for the analysis of UA curvature in the sagittal dimension. Since the titration period (140 ¡ 87 days) of the OA in order to avoid known side-effects [4] is obviously longer than with nCPAP, where titration of nasal pressure is typically achieved in one night, it is acknowledged that this longer time period is a limitation of OA therapy especially when a rapid therapeutic response is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the fact that fat deposition increases tongue dimensions (length Eb-TT, height TgH, TgH Dorsum, and Eb-Tg Dorsum) but not necessarily its posterior projection into the retroglossal area. While the impact of larger tongues on the restriction of the retroglossal space is not evident in the upright position, it is likely to be more significant in the supine posture due to the sagging of the base of the tongue against the PPW, gravitational pull [64, 65], and the hypotonicity of the genioglossal muscle during sleep [66]. …”
Section: Discussionmentioning
confidence: 99%
“…A cephalometric study performed during stage 1-2 sleep revealed significant changes compared with the awake state: the mandible rotated clockwise, the hyoid bone moved downward toward the thorax, the anteroposterior UA dimension decreased, and the cervical bone was displaced anteriorly toward the chin [50]. The posture of the mandible periodically changes according to the sleep stage across [47].…”
Section: Activity During Sleepmentioning
confidence: 99%